PROSES BERPIKIR SISWA KELAS VII SEKOLAH MENENGAH PERTAMA DALAM MEMECAHKAN MASALAH MATEMATIKA MATERI POKOK BANGUN DATAR BERDASARKAN PERSPEKTIF GENDER - Sukowiyono Sukowiyono; Tri Atmojo Kusmayadi; Imam Sujadi (Jurnal Pembelajaran Matematika, 2013)
Abstract: This research aimed to find out the thinking process VII Graders of Junior High School in mathematics problem solving in plane geometry. This study was a descriptive qualitative research. The subject of research was the VII graders of SMP (Junior High School) Muhammadiyah 1 Surakarta consisting of four students. The subject was selected based on gender, mathematics ability and either spoken or written communication fluency. The data collection was conducted using think aloud technique. Data analysis was conducted based think aloud protocol. Then, time triangulation was conducted between the first and the second problems, and then method triangulation was done to obtain valid research subject data.This research finally provide the student’s thinking process as follows. The male students: 1) understand and analyze the problem by mentioning what they know and what asked, the thinking process used is the process of establishing cognition, 2) design and plan solution, used the thinking process of opinion establishment, 3) look for solution to problem solving, used thinking process of decision making and conclusion drawing, 4) examine the solution, could estimate mentally by writing nothing he did, the thinking process in this step was decision making thinking process. Female students: 1) understand the problem using thinking process of establishing cognition, to mention easily and correctly what they know in the problem and to mention what asked, 2) design and plan the solution using thinking process of opinion establishment and cognition establishment. could link the what known and what asked, 3) look for solution to problem using thinking process of decision making and conclusion drawing, 4) examine the solution, it is consistent with the students that can examine and investigate the prepared solution.Keywords: thinking process, mathematics problem solving, gender.